YOGA EFFECTS ON PHYSICAL ACTIVITY AND SEXUAL SATISFACTION AMONG THE IRANIAN WOMEN WITH MULTIPLE SCLEROSIS: A RANDOMIZED CONTROLLED TRIAL. - Najafi doulatabad, Shahla; Mohebbi, Zinat; Noorian, Khirollah (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Multiple Sclerosis (MS) is a chronic and disabling disease resulting in disabilities in young and middle-aged persons. In this study, researchers explored the effect of yoga techniques on physical activities and sexual function among some Iranian women with MS.Materials and Methods: In this study, 60 Iranian women with multiple sclerosis (MS) were placed in two equally divided control and case groups through random selection to assess pre- and post- effects of yoga exercises on their physical activities and sexual satisfaction levels. Women in case group were offered a series of yoga training and exercises for 3 months, which consisted of 8 sessions per month for 60 to 90 minutes at each session. Yoga training program included the 3 principles of slow motions (Hatayoga), respiratory exercises (Pranayama) and centralization to control mind via meditation, expansion and stasis (Rajayoga). After 3 months both groups were surveyed using the initial questionnaire to evaluate and compare findings with the base-line data.Results: Researchers found significant statistical difference in physical activity and sexual satisfaction levels among the women in case group (P=0.001). Women in case group showed improvement in physical ability while women in control group manifested exacerbated symptoms.